Persepsi Guru Biologi terhadap Implementasi Kurikulum Merdeka di SMA Negeri se-Kota Metro: (Biology Teachers' Perceptions on the Implementation of the Independent Curriculum at State High Schools in Metro City) - Latifah, Nurul; Hayati, Dwi Kurnia (BIODIK, 2023)
The change of the original curriculum from the Curriculum 2013 to the Merdeka Curricuum Eelicits a variety of perceptions or responses from teachers, students, and parents of students. The study aims to understand the perceptions of biology teachers about the application of the Merdeka Curriculum in the six state high schools in the city of Metro. The research methods used were six biology teachers from each school. Data capture techniques include interviews, observations, documentation, and data validation techniques. The resuls show that each biology teacher at the state hig school in Metro City has a different perception of the implementation of the Merdeka Curriculum, which is because some eachers have difficulties implementing of the Merdeka Curriculum. Key words: Implementation, Merdeka Curriculum, Teacher perception Abstrak. Pergantian Kurikulum yang semula dari Kurikulum 2013 menjadi Kurikulum Merdeka menuai berbagai persepsi atau tanggapan mulai dari para guru, siswa maupun orang tua siswa. Penelitian ini bertujuan untuk mengetahui persepsi guru biologi terhadap penerapan Kurikulum Merdeka di enam SMA Negeri yang ada di kota Metro. Metode penelitian yang digunakan adalah kualitatif deskriptif, dan subjek penelitiannya adalah enam orang guru biologi dari masing-masing sekolah. Teknik pengambilan data melalui wawancara, observasi, dokumentasi, danÂ  teknik penjamin keabsahan data menggunakan triangulasi teknik. Hasil penelitian menunjukkan bahwa setiap guru biologi di SMA Negeri kota Metro memiliki persepsi yang berbeda-beda terhadap implementasi kurikulum merdeka, hal ini dikarenakan beberapa guru mengalami kendala dalam pengimplementasian kurikulum merdeka. Kata kunci: Implementasi, Kurikulum Merdeka, Persepsi Guru